2013
DOI: 10.1038/onc.2013.412
|View full text |Cite
|
Sign up to set email alerts
|

HAI-2 suppresses the invasive growth and metastasis of prostate cancer through regulation of matriptase

Abstract: Dysregulation of cell surface proteolysis has been strongly implicated in tumorigenicity and metastasis. In this study, we delineated the role of hepatocyte growth factor activator inhibitor-2 (HAI-2) in prostate cancer (PCa) cell migration, invasion, tumorigenicity and metastasis using a human PCa progression model (103E, N1, and N2 cells) and xenograft models. N1 and N2 cells were established through serial intraprostatic propagation of 103E human PCa cells and isolation of the metastatic cells from nearby l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 43 publications
1
57
1
3
Order By: Relevance
“…Although the previous report indicated that matriptase activation undergoes an autoactivation process in vitro (22), this is the first report of matriptase activation by another membrane-anchored serine protease, TMPRSS2, in response to androgens. Moreover, recent reports have also shown that downregulated expression of two cognate inhibitors of matriptase (HAI-1 and HAI-2) is correlated with the progression of prostate cancer and other cancers (34)(35)(36)(37) and occurs in parallel with matriptase activation and cancer cell invasion (24,38). Thus, reduced levels of HAI-1 or HAI-2 contribute to matriptase activation and cancer progression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the previous report indicated that matriptase activation undergoes an autoactivation process in vitro (22), this is the first report of matriptase activation by another membrane-anchored serine protease, TMPRSS2, in response to androgens. Moreover, recent reports have also shown that downregulated expression of two cognate inhibitors of matriptase (HAI-1 and HAI-2) is correlated with the progression of prostate cancer and other cancers (34)(35)(36)(37) and occurs in parallel with matriptase activation and cancer cell invasion (24,38). Thus, reduced levels of HAI-1 or HAI-2 contribute to matriptase activation and cancer progression.…”
Section: Discussionmentioning
confidence: 96%
“…The details about tissue assays were described in Supplementary Information. Immunohistochemical staining was carried out as previously described (24). The immunohistochemical images were scored by the percentage (P) of staining of tumor cells or prostate epithelial cells (0, <10%; 1, 10%-25%; 2, 25%-50%; 3, 50%-75%; 4, >75%) and by the intensity of staining (I; 0, negative staining; 1, weak staining; 2, moderate staining; and 3, strong staining).…”
Section: Immunohistochemical Staining Of Prostate Tissue Sectionsmentioning
confidence: 99%
“…Recently, some reports indicate SPINT2 as a tumor suppressor gene, as hypermethylation of its promoter is a frequent cause of SPINT2 downregulation (Fukai et al 2003;Schuster et al 2003;Chiba et al 2005;Morris et al 2005;Kongkham et al 2008;Morris et al 2008;Tung et al 2009;Dong et al 2010). In PCa, a significant decrease of SPINT2 protein has been reported in poorly differentiated tumors as compared with lower Gleason score tumors (Bergum et al 2010;Tsai et al 2013). However, the process underlying SPINT2 down-regulation in PCa is still unknown.…”
Section: Research-article2015mentioning
confidence: 99%
“…Activated HGF/SF binds to its receptor tyrosine kinase MET to induce dimerization and initiate phosphorylation cascades leading to comprehensive cellular changes that, in the deregulated context of cancer, drive malignant transformation and progression (73). HAI2 has been found to be a natural tumor suppressor in renal cell carcinoma (74), breast cancer (75,76), and prostate cancer (77,78), the loss of which leads to tumor growth and progression attributable at least in part to increased MET signaling. We have found mesotrypsin to be up-regulated with progression in prostate cancers and to contribute to invasion and metastasis (10), and it is highly plausible that these activities of mesotrypsin may be mediated at least in part through cleavage and inactivation of HAI2, with resulting increases in HGF/SF activation and MET signaling.…”
Section: Discussionmentioning
confidence: 99%